Identificação de ilhas de calor na área urbana de Ilha Solteira - SP através da utilização de geotecnologias - da Costa, Douglas F. [UNESP]; Silva, Helio Ricardo [UNESP]; Peres, Leonardo de F. (Soc Brasil Engenharia Agricola, 2010)
With climate change expected in the coming decades, scientists suggest that one of the consequences is the increase in average temperatures and also the increasing number of hot days, which will enhance the thermal discomfort in the population. Therefore, this study aimed to identify the main thermal variations in the urban area of Ilha Solteira-SP, Brazil. The methodology involved the transformation of Landsat TM data into values of surface temperature and their comparison to distinct urban land use. The results showed the presence of variations in surface temperatures in the different regions of the municipality. The areas that have higher amount of vegetation, such as the forest area of the zoo and the recreation area, showed surface temperatures between 21 degrees C and 23 degrees C. The areas that showed higher temperatures (41 degrees C to 44 degrees C) were located in the regions in which occur the largest percentages of classes buildings and paved-building, thus characterizing the phenomenon of heat islands. These results could be used to support urban planning strategies to minimize the effects of thermal discomfort of the areas identified as heat islands.
Identification of urban heat islands in Ilha Solteira-SP municipality using geotecnologies
Keywords: remote sensing; Landsat-5; thermal infrared; atmospheric correction; thermal discomfort